Access Denied: Low Mentoring of Women and Minority First-Time Directors and Its Negative Effects on Appointments to Additional Boards - McDonald, Michael L.; Westphal, James D. (Academy of Management Journal, 2013)
This study contributes to the literature on women and minorities in corporate leadership by developing theory that can help to explain the persistent underrepresentation of women and minorities among those who are seen as members of the "corporate elite" because they hold multiple corporate board seats. Our conceptual framework suggests how disadvantages in the receipt of mentoring regarding prevailing norms in the corporate elite are negatively affecting the ability of women and minorities to secure multiple board appointments. Our theory explains why women and minority first-time directors receive comparatively less mentoring regarding a core norm in the corporate elite that outside directors should avoid exercising independent control over firm strategy. Our theory also explains why lower levels of mentoring result in women and racial minority first-time directors receiving relatively fewer appointments to other boards. This study also contributes to the corporate leadership literature by explaining how fundamental intergroup biases are negatively impacting the demographic diversity of the corporate elite. This article further highlights a specific social mechanism that undermines efforts to move toward more meritocratic outcomes in corporate leadership whereby those who are relatively qualified will have greater success in rising to the highest-level positions in the corporate world.